2020
DOI: 10.1016/j.bja.2020.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on technology-driven preoperative exercise interventions: are we there yet?

Abstract: Use of a perioperative web-based exercise program for a patient with Barrett's carcinoma scheduled for esophagectomy. Case Rep Oncol 2019; 12: 755e64 15. Olivero CF, Collado LM, Sarceda JJ, et al. The use of a smartphone application improves postoperative outcomes in patients undergoing lung cancer resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Waterland et al 2020 [ 43 ] found 72% of patients prior to oncological surgery would prefer exercise prehabilitation in a home-based environment. Although initial work has been done to optimise the home-based service, especially in the wake of the COVID-19 pandemic, further scoping needs to occur involving app-based, web-based or virtual reality methodologies to improve treatment fidelity when exercising at home [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Waterland et al 2020 [ 43 ] found 72% of patients prior to oncological surgery would prefer exercise prehabilitation in a home-based environment. Although initial work has been done to optimise the home-based service, especially in the wake of the COVID-19 pandemic, further scoping needs to occur involving app-based, web-based or virtual reality methodologies to improve treatment fidelity when exercising at home [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the most compelling evidence is reported in lung cancer patients, where preoperative exercise was shown to be effective in reducing the rate of postoperative complications and length of hospital stay, for other groups of patients undergoing oncological surgery, the evidence is less compelling. 32 In analogy with observations from other groups of patients suffering from cancer a marked loss of muscle mass along with worsening cardiorespiratory fitness and HRQoL during neoadjuvant treatment has been observed in esophagogastric cancer patients. 33,34 While this provides a strong rationale for pre-surgical interventions in this group there are thus far only limited, albeit encouraging, results on the feasibility and effectiveness of prehabilitation in these patients.…”
Section: Rehabilitation For Other Groups Of Patients Undergoing Oncol...mentioning
confidence: 99%
“…Previous studies suggest that the intensity of exercise required to facilitate cardiorespiratory exercise benefits may be unable to be achieved within the home-based setting without supervision (Edbrooke et al 2019 ). Therefore, it may be essential to adapt existing interventions to facilitate improved exercise fidelity and patient adherence to exercise programs within the major surgery group such as the inclusion of a technology-driven exercise interventions to more accurately monitor exercise program adherence, such as those described by Steffens et al ( 2020 ).…”
Section: Discussionmentioning
confidence: 99%